EFEKTIVITAS PERATURAN GUBERNUR TENTANG STANDAR OPERASIONAL PROSEDUR (SOP) ADMINISTRASI PEMERINTAHAN DI PEMERINTAH DI PEMERINTAH DAERAH PROVINSI SULAWESI TENGAH - Muhammad, Tedi (Katalogis, 2017)
The purpose of this study was to determine how the effectiveness of Governor Regulation on Standard Operating Procedures (SOP) Administrative Governance in Central Sulawesi Provincial Government, who studied based on theoretical models measure the effectiveness of Duncan by using variables: 1). Achievement, 2). Integration, 3). Adaptation. This type of research used qualitative decision-informants purposively and the number of informants as much as 5 people with data collection techniques, 1). Observation, 2). Interviews, 3). Documentation. Catalysts data using Miles and Huberman opinion. Results is Indicates that the preparation of Standard Operating Procedures (SOP) Administration In Central Sulawesi Provincial Government does not operate effectively under Regulation Governor of Central Sulawesi Central No. 17 Year 2012 on Standard Operating Procedures in the Government of Central Sulawesi province. Judging from the three measures of effectiveness proposed by Duncan, who runs a good criterion, namely adaptation. While the criteria have not been running well in the preparation of Standard Operating Procedures (SOP) Administration in the Government of Central Sulawesi province, namely Achievement and Integration because of ineffective socialization preparation of Standard Operating Procedures Administration that resulted in delayed ratification of the Standard Operating Procedure Administration, which should be legalized in 2016.